Scaffolding Narrative Reading through Literature Circles and the Teaching and Learning Cycle: Evidence from Indonesian EFL Classrooms - Anggraini, Adinda Keisha; Yanto, Elih Sutisna (Universitas Syiah Kuala, 2025)
This study investigates how integrating Literature Circles with the Teaching and Learning Cycle enhances junior secondary English as a Foreign Language students engagement, comprehension, and motivation in extensive reading of narrative texts. Using a qualitative classroom action research design with phenomenological orientation, data were collected through semi-structured interviews, reflective journals, and classroom observations. The intervention followed four Teaching and Learning Cycle stagesBuilding Knowledge of the Field, Modelling of the Text, Joint Construction of the Text, and Independent Construction of the Textcombined with rotating Literature Circle roles to scaffold comprehension and collaboration. Findings reveal that students progressed from supported participation to independent analysis, showing gains in vocabulary noticing, inferential reasoning, and critical response. Students also reported heightened intrinsic motivation, confidence, and ownership of learning, facilitated by structured peer interaction and equitable participation. Challenges such as time constraints, text difficulty, and performance anxiety emerged but also suggested avenues for refinement in instructional design. This study contributes conceptually by bridging constructivist, sociocultural, and genre-based perspectives, pedagogically by operationalizing scaffolding through structured roles, and contextually by adding evidence from Indonesian junior secondary classrooms. These findings highlight the potential of Literature Circles integrated with the Teaching and Learning Cycle as a sustainable model for student-cantered reading instruction and provide directions for future research on scalability, digital mediation, and application across genres